2013
DOI: 10.1152/ajprenal.00642.2012
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin-2 and BNIP3 regulate autophagy and mitophagy in renal tubular cells in acute kidney injury

Abstract: Autophagy is a cellular recycling process induced in response to many types of stress. However, little is known of the signaling pathways that regulate autophagy during acute kidney injury (AKI). Bcl-2/adenovirus E1B 19 kDa-interacting protein (BNIP)3 and sestrin-2 are the target proteins of hypoxia-inducible factor (HIF)-1␣ and p53, respectively. The aim of this study was to investigate the roles of BNIP3 and sestrin-2 in oxidative stressinduced autophagy during AKI. We used rat ischemia-reperfusion injury an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
129
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(137 citation statements)
references
References 48 publications
8
129
0
Order By: Relevance
“…Just recently, increased expression of sestrin 2 was reported in renal proximal tubules in a model of renal ischemia-reperfusion injury (16). In addition, increased sestrin 2 expression was shown in cultured renal tubular cells (NRK-52E cells) exposed to oxidative stress (16). Taken together, the results of the present study show that in contrast to other cell types where sestrin 2 expression is related to stressors, sestrin 2 is constitutively expressed in normal adult PECs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Just recently, increased expression of sestrin 2 was reported in renal proximal tubules in a model of renal ischemia-reperfusion injury (16). In addition, increased sestrin 2 expression was shown in cultured renal tubular cells (NRK-52E cells) exposed to oxidative stress (16). Taken together, the results of the present study show that in contrast to other cell types where sestrin 2 expression is related to stressors, sestrin 2 is constitutively expressed in normal adult PECs.…”
Section: Discussionsupporting
confidence: 74%
“…Sestrin 2 is a novel p53 target protein that accumulates in stressed cells (18). Just recently, increased expression of sestrin 2 was reported in renal proximal tubules in a model of renal ischemia-reperfusion injury (16). In addition, increased sestrin 2 expression was shown in cultured renal tubular cells (NRK-52E cells) exposed to oxidative stress (16).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the accumulating data has only shown that SESN2 expression can be upregulated in response to oxidative stress at the transcriptional level. 24,46,49,50 However, for the first time, we were able to demonstrate that Figure 10. SESN2 suppresses prolonged NLRP3 activation by preserving mitochondrial homeostasis through mitophagy induction.…”
Section: Discussionmentioning
confidence: 70%
“…Consistent with this concept, Ishihara et al have reported the involvement of autophagy molecules sestrin-2 and BNIP-3 in the acutely injured kidney. 37 Mitochondrial fusion is mediated by proteins including mitofusin 1, mitofusin 2 (Mfn2), and optic atrophy 1. Recent studies have demonstrated that deletion of Mfn2 selectively in renal epithelial cells leads to mitochondrial fragmentation and apoptosis after ATP depletion in vitro.…”
Section: Mitochondriamentioning
confidence: 99%